Determinants of Technology Adoption: Evidence from the Chinese Banking Industry. Issue 11 (2nd September 2021) - He, Dongwei; You, Kai; Li, Wenqing; Wu, Jun
ABSTRACT: The decision on online banking adoption is a strategic choice by banks with multiple purposes. Using panel data on banks with hand-collected information on adoption decisions from 2002 to 2016, this article is the first to examine the determinants of online banking adoption in China. We first construct a theoretical model to illustrate banks' online service adoption strategy and then test the determinants of online banking adoption decisions. Our model compares the patterns of online banking adoption decisions at large national banks and small banks. The model and empirical results show that banks with a larger geographic market adopt online banking earlier, and banks' online banking adoption may be motivated by having competitors that have already adopted this technology. We also find evidence that online banking is a substitute for physical branches. Our results shed light on the banks' effective management of online and offline services.